Answer: The answer is the first one, angle JLK
Step-by-step explanation:
Solve for x. Isolate the x. Note the equal sign. What you do to one side, you do to the other. Do the opposite of PEMDAS.
First, multiply 3 to both sides
6(3) = ((x + 2)/3)(3)
18 = x + 2
Finally, isolate the x. Subtract 2 from both sides
18 (-2) = x + 2 (-2)
x = 18 - 2
x = 16
16 is your answer for x
hope this helps
Answer:
c. 10
Step-by-step explanation:
Eliminate parentheses using the distributive property.
3(b+4) -2(2b+3) = -4 . . . . given
3b +12 -4b -6 = -4 . . . . . parentheses eliminated
-b +6 = -4 . . . . . . . . . . . . collect terms
-b = -10 . . . . . . . . . . . . . . subtract 6
b = 10 . . . . . . . . . . . . . . . . multiply by -1
_____
The rules of equality require that any operation you perform on one side of the equal sign must also be done on the other side. So when we say "subtract 6", we assume you know that means "subtract 6 from both sides of the equation", for example.
The answer is 86
Following PEMDAS, which is:
parentheses
exponents
multiplication
division
addition
subtraction
I found that the answer was 86